MLPA analysis of 32 foetuses with a congenital heart defect and 1 foetus with renal defects - pilot study. The significant frequency rate of presented pathological CNV - Štefeková, Andrea; Čapková, Pavlína; Čapková, Zuzana; Curtisová, Václava; Srovnal, Josef; Mracká, Enkhjargalan; Klásková, Eva; Procházka, Martin (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2022)
AIMS: The aim of this retrospective study was to determine the detection rate of the pathogenic copy number variants (CNVs) in a cohort of 33 foetuses - 32 with CHD (congenital heart defects) and 1 with kidney defect, after exclusion of common aneuploidies (trisomy 13, 18, 21, and monosomy X) by karyotyping, Multiplex ligation - dependent probe amplification (MLPA) and chromosomal microarray analysis (CMA). We also assess the effectivity of MLPA as a method of the first tier for quick and inexpensive detection of mutations, causing congenital malformations in foetuses. METHODS: MLPA with probe mixes P070, P036 - Telomere 3 and 5, P245 - microdeletions, P250 - DiGeorge syndrome, and P311 - CHD (Congenital heart defects) was performed in 33 samples of amniotic fluid and chorionic villi. CMA was performed in 10 relevant cases. RESULTS: Pathogenic CNVs were found in 5 samples: microdeletions in region 22q11.2 (≈2 Mb) in two foetuses, one distal microdeletion of the 22q11.2 region containing genes LZTR1, CRKL, AIFM3 and SNAP29 (≈416 kb) in the foetus with bilateral renal agenesis, 8p23.1 (3.8 Mb) microdeletion syndrome and microdeletion in area 9q34.3 (1.7 Mb, Kleefstra syndrome). MLPA as an initial screening method revealed unambiguously pathogenic CNVs in 15.2 % of samples. CONCLUSION: Our study suggests that MLPA and CMA are a reliable and high-resolution technology and should be used as the first-tier test for prenatal diagnosis of congenital heart disease. Determination of the cause of the abnormality is crucial for genetic counselling and further management of the pregnancy.
Keywords: pilotní projekty; Pregnancy; těhotenství; Heart Defects, Congenital; vrozené srdeční vady; Retrospective Studies; plod; retrospektivní studie; lidé; DNA Copy Number Variations; Female; ženské pohlaví; variabilita počtu kopií segmentů DNA; transkripční faktory; Fetus; Humans; Transcription Factors; Pilot Projects